ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN SYARIâAH (IMPLEMENTASI PADA PERJANJIAN BAKU DI BAITUL MAAL WA ATTANWIL/BMT KOTA METRO) - Murdiana, Elfa (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
ABSTRACTÂ The existence of a contract cannot be separated from the basics of tying, to reach a consensus in the agreement, the parties should have the same inclination, good and gives you the freedom to decide something that should be included in the agreement/contract, without any compulsion, for agreement this will occur as a law for the parties to agree to make it. The basic substance is an illustration of the principle of freedom of contract for which the perspective of law in Indonesia implementation must be framed by other Articles in the framework of the legal system and the full contract round. These articles are article 1320 BW, 1335BW, 1337-1339BW and 1347 BW. But in fact the implementation of the principle of freedom of contract only to the determination of the amount of profit sharing clause for clause contained in a contract already programmed into the existing financial system.Â Keywords: Freedom of contract, contracts, BMT.